Convention on the Rights of the Child (Journal of Parents and Teachers, 2026)
This article sets out the official text of the Convention on the Rights of the Child, adopted at the 44th session of the United Nations General Assembly.
Keywords: Convention on the Rights of the Child; United Nation General Assembly